INTEGRASI NILAI MULTIKULTURAL DALAM PENDIDIKAN AGAMA ISLAM: STUDI PERBANDINGAN KONSEPTUAL ANTARA PEMIKIRAN BARAT DAN TRADISI ISLAM - Maulana Malik Ibrahim; Muhammad Hasyim Asyari; Mambaul Usulil Khikmah; Muhammad Jakfar; Muhammad Masyhuri; Isyatil Fitri (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2025)
This conceptual and comparative study examines the integration of multicultural values within Islamic Religious Education (PAI) as an essential foundation for fostering inclusive, tolerant, and humanistic education. It aims to explore how the principles of multicultural education in Western thought correspond to and differ from the fundamental Islamic teachings derived from the Qur’an and Hadith. The discussion focuses on the compatibility between Western multicultural values such as equality, pluralism, and social justice and Islamic values of adl (justice), tasamuh (tolerance), tawazun (balance), and tawassuth (moderation). The study concludes that the integration of multicultural values into Islamic education should be carried out conceptually through curriculum development, pedagogical strategies, and moral exemplarity based on Qur’anic guidance and propethic and practice. This research uses a literature review method through searching national and international scientific journals, books on multicultural education theory, classical and contemporary PAI literature, and academic articles from 2015–2024. The analysis was conducted using a descriptive-comparative approach to identify conceptual similarities and differences between the two perspectives.